The Effect Of Good Corporate Governance On Stock Returns In The Non- Cyclical Sector Indexed In Lq45 - Ramadhan, Dafa Munif; Krisnawati, Astrie (eProceedings of Management, 2023)
The company will be very careful in publishing financial statements and other matters relating to companyperformance because it will be a consideration of investors in making investment decisions. The main objective of thisresearch is to analyze the effect of good corporate governance, which consists of Board of Directors, IndependentCommissioner, and Audit Committee, on Stock Returns either partially or simultaneously. he population in this studyare Non-Cyclical sector companies indexed LQ45 2017-2021. The data processing method used in this study is aquantitative method in the form of descriptive statistical analysis, panel data regression analysis, classical assumptiontest (normality test, multicollinearity test and heteroscedasticity test) and hypothesis testing using the coefficient ofdetermination test, statistical t test, and statistical F test. The results of this study indicate that simultaneouslyindependent commissioners, audit committees, and boards of directors have no effect on stock returns. While partially,there are no independent variables that affect stock returns.Keywords-Stock Returns, Board of Directors, Independent Commissioner, Audit Committee.